Differences in patience and its components between individuals with depressive symptoms, generalized anxiety symptoms, and normal individuals - Al-Zaidani, Ahmed Mohammed (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to investigate the differences in patience and its components between three community groups of people with depressive symptoms, symptoms of generalized anxiety and normal people. Method and tools: The researcher used the descriptive approach, and (47) people with depressive symptoms, (39) people with generalized anxiety symptoms, and (64) normal healthy people participated in this study. The mean age of the participants is (29.13) And with a standard deviation (10.37). The researcher used two scales: The patience scale prepared by the author, and the hospital scale for anxiety and depression developed by Zigmond and Snaith (1983). The results showed a negative and statistically significant relationship of the patience and its components (spiritual transcendence, patience, reassurance, and Postponement) with both depression and general anxiety. The study also found that there are statistically significant differences between the three groups in patience and its components (spiritual transcendence, patience, reassurance, and Postponement), as the normal people were more patient than the two groups of patients. The study reached a number of recommendations, the most important of which is that psychologists use strategies for training patience in treating depression and anxiety patients. And the study of patience and its components in other psychological disorders, and in pathological samples.